Plasma myeloperoxidase: association with atrial fibrillation progression and recurrence after catheter ablation - Liu, Jingmeng; Lin, Changjian; Zhou, Taojie; Bao, Yangyang; Xie, Yun; Wei, Yue; Luo, Qingzhi; Ling, Tianyou; Pan, Wenqi; Zhang, Ning; Lu, Lin; Wu, Liqun; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Myeloperoxidase (MPO), released by activated neutrophils, is significantly increased in atrial fibrillation (AF). MPO may play a role in the progression of atrial fibrillation and further involved in AF recurrence after catheter ablation. We compared plasma MPO levels in paroxysmal and persistent AF and explored their role in AF recurrence after catheter ablation. Methods Plasma MPO levels were measured in consecutive patients with paroxysmal AF (n = 225) and persistent AF (n = 106). Samples of patients were collected from the femoral vein during catheter ablation and all patients included were followed up after catheter ablation. Results Plasma MPO levels increased from paroxysmal AF to persistent AF patients (56.31 [40.33–73.51] vs. 64.11 [48.65–81.11] ng/ml, p < 0.001). MPO significantly correlated with left atrium volume (LAV) and there existed a significant interaction between the two in relation to AF recurrence (p for interaction <0.05). During a median follow-up of 14 months, 28 patients with paroxysmal AF (12.44%) and 27 patients with persistent AF (25.47%) presented with recurrence after catheter ablation. The percentage of recurrence increased stepwise with increasing tertiles of MPO levels in both paroxysmal AF and persistent AF. MPO levels remained independently associated with AF recurrence after adjusting for potential confounding variables. Conclusion MPO levels were higher in persistent AF than in paroxysmal AF and MPO was positively correlated with LAV in AF. Elevated MPO levels may predispose a switch in AF phenotype and AF recurrence after catheter ablation.